A interiorização dos institutos federais : um estudo de caso sobre a implantação do campus Venda Nova do Imigrante - Feitosa, Patrícia de Almeida (2013)
This research aims the study of the implementation of the Venda Nova do Imigrante campus. It has been created by the interiorization project of the IFES – Instituto Federal do Espírito Santo according to the federal law number 11.892 from December 29, 2008. The investigation happened through a case observation. It focused on the analysis of social implications of the implementation of this legal ordering in a regional and social level. Interviews and questionnaires were used as tools to collect these data. As well as the analisis of laws and institutional documents. The results of this research showed the following challenges: the autorization for the construction of the campus, the demand for the appropriate land used for the construction of the campus, the purchase of materials and equipments for the laboratories, and also the lack of personnel (faculty and administration). Considering the main social development possibilities were identified the following issues: courses offered are in line with regional and local economic vocation; there is the possibility of fixation of graduates of the courses on the region; most of the students in the campus have come from public schools and, the campus substantially increased the number of high school vacancies in the region